Legally Queer: The Construction of Sexuality in LGBQ Asylum Claims. Issue 4 (7th November 2016) - Vogler, Stefan
Abstract : Using court decisions, interviews with legal actors, and ethnographic observations, this paper analyzes the development of sexual identity classifications for sexual minorities seeking asylum in the United States and argues that the adjudication of such claims works to consolidate and regulate sexual identities but also creates possibilities for recognizing marginalized queer identities. Asylum seekers must prove their sexual identities, and immigration officials must classify claimants as belonging to a protected group. At the inception of queer asylum law in 1990, protected categories were highly circumscribed, but the indeterminacy of the law allowed advocates and asylum seekers to challenge existing categories and stake out new claims based on their sexualities. Against the backdrop of extant criticisms of the asylum process for queers, this paper suggests that the way asylum law has been elaborated, adapted, and interpreted, particularly in approximately the past decade, offers possibilities for making unique identity claims that are not recognized in existing scholarship.